A 6-Month Open-Label Study of Vortioxetine among Cancer Patients with Major Depressive Disorder (MDD) - Chong Guan, Ng; Aya Ahmed, Abousheishaa; Sue Yin, Low; Nor Zuraida, Zainal; Kai Shin, Thong; Azizul, Awaluddin; Tsui Huei, Loo; Sapini, Yacob; Nik Ruzyanei, Nik Jaafar; Nur Iwana, Abdul Taib; Nurul Ain, Mohamad Kamal; Fuad, Ismail; et al. (The Asian Pacific Journal of Cancer Prevention (APJCP), 2023)
Objective: Vortioxetine is a monoaminergic drug with a novel multimodal mechanism of action. We investigated its efficacy on depressive symptoms, cognitive function, and quality of life among cancer patients.Methods: In this multicenter, open-label, single-arm, observational study, patients received flexible doses of Vortioxetine for a period of six months. All participants were assessed at baseline and scheduled for monitoring at weeks 2, 4, 8, 12, 16, 20, and 24. Depression severity was assessed using Montgomery-Asberg Depression Rating Scale (MADRS) and the Clinical Global Impression (CGI) scale. The Perceived Deficiency Questionnaire (PDQ-5) assessed the perceived cognitive difficulties in concentration, executive functioning, and memory. The European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire (EORTC) was used to assess the patients’ quality of life. Side effects of vortioxetine were monitored using the Antidepressant Side-Effect Checklist (ASEC). Results: Patients experienced a reduction in MADRS scores from 29.89 ± 5.997 at baseline to 11.59 ± 4.629 by Week 24. The PDQ-5 scores showed significant change from Week-4, whereas the EORTC role, emotional, and cognitive functioning scores showed a significant change from Week 2 onwards. CGI-Severity scores decreased from a baseline of 4.39 ± 0.746 to 2.41 ± 1.085 by Week 24. During the 24-Weeks of therapy, around three-quarters of the patients (73.3%) had one or more adverse events reported on the ASEC. The most frequently reported TEAEs were dry mouth, insomnia, somnolence, and headache, with more than a 30% incidence rate. Conclusion: Vortioxetine seems promising in the management of depression and enhancement of cognitive function and quality of life of cancer patients with Major Depressive Disorder.